Israel Continues to Expand Its Settlements - A. Krylov (Международная аналитика, 2015)
This article provides a detailed analysis of the new trends of development of Israeli settlements in the West Bank, including East Jerusalem and the Jordan Valley, the Gaza Strip, and the Golan Heights. Since 1967, Israel has established about 150 settlements in the West Bank in addition to some 100 «outposts» or illegal settlements without Israeli official authorization. Now the settler population has estimated at over 520,000; the annual average rate of growth during the past decade was 5.3%, compared to 1.8% for the Israeli population as whole. As is known, after the Annapolis Conference held on 27 November 2007 Israel under the pressure from the international community announced officially not to create new settlements. But the Israeli authorities are now actively expanding in the occupied Palestinian territory, «border zones» or «buffer zones» in order to confiscate Palestinian land between the separation fence and the Palestinian communities located at a sufficient distance away from the wall.This study reveals the new forms and methods, aims and objectives of the Israeli official settlement policy and indicates a negative influence of the settlement factor on the Israeli-Palestinian negotiating process, political and socio-economic situation in the Middle East. The author do not exclude the possibility that if the political decision based on the principle of coexistence of two States not be achieved in the nearest future we may see soon on the map of the West Bank some Palestinian enclaves completely isolated like the Gaza Strip now. It is obvious that in the Jordan Valley and another parts of «zone C» Israel aims to do that it did in the area, where the block of settlements Maale Adumim is located, which Israeli politicians now consider an integral part of the territory of the State of Israel.